Identification of Erosional Terraces on Seamounts: Implications for Interisland Connectivity and Subsidence in the Galápagos Archipelago - Schwartz, Darin M.; Soule, S. Adam; Wanless, V. Dorsey; Jones, Max P. (Frontiers in Earth Science, 2018)
Shallow seamounts at ocean island hotspots and in other settings may record emergence histories in the form of submarine erosional terraces. Exposure histories are valuable for constraining paleo-elevations and sea levels in the absence of more traditional markers, such as drowned coral reefs. However, similar features can also be produced through primary volcanic processes, which complicate the use of terraced seamounts as an indicator of paleo-shorelines. In the western Galápagos Archipelago, we utilize newly collected bathymetry along with seafloor observations from human-occupied submersibles to document the location and depth of erosional terraces on seamounts near the islands of Santiago, Santa Cruz, Floreana, Isabela, and Fernandina. We directly observed erosional features on 22 seamounts with terraces. We use these observations and bathymetric analysis to develop a framework to identify terrace-like morphologic features and classify them as either erosional or volcanic in origin. From this framework we identify 79 erosional terraces on 30 seamounts that are presently found at depths of 30 to 300 m. Although intermittent connectivity between the islands has been hypothesized, the depths of these erosional terraces in the Santiago region are the first direct evidence of paleo-connectivity in the modern archipelago. Collectively, the terraces have non-randomly distributed depths. We suggest that peaks in the distribution of terrace depths likely represent long durations of exposure (i.e. sea-level still or lowstands). By comparing these peaks to those of subsidence adjusted sea-level curves, we identify the average subsidence rate that best reproduces the observed terrace distributions. These rates are 0.2-0.4 m/kyr for this portion of the central Galápagos, since the formation of the seamounts, consistent with previous independent estimates. Using these subsidence rates and evidence for erosional terraces at depths up to 300 m, we conclude that all islands in the central archipelago have been intermittently connected starting between 435 and 900 ka. Individual island pairs have likely been repeatedly connected for short intervals since that time.